Properties and environmental impact of building foundation pit backfilling materials containing iron and steel solid waste - Zhang, Hongze; Qi, Yang; Jing, Jianlin; Wang, Changlong; Zhou, Yongxiang; Zhang, Kaifan; Zheng, Yongchao; Zhai, Yuxin; Liu, Feng (Frontiers in Earth Science, 2023)
Introduction: In order to promote the comprehensive utilization of iron and steel solid waste, steel slag (SS), granulated blast furnace slag (GBFS), and flue gas desulfurization gypsum (FGDG) were used as raw materials to replace cement to prepare the full solid waste premixed solidified agent (PSA). Then PSA, iron ore tailings (IOTs), and water were mixed to prepare building foundation pit backfilling materials (BFPBM). Methods: Various tests were conducted to investigate the effects of SS fineness, SS content and mixing ratio of PSA on the properties of PFPBM, including mechanical property test, X-ray diffraction (XRD), scanning electronic microscopy (SEM), energy dispersive spectrometry (EDS) and synthetic precipitation leaching procedure (SPLP). The stability of the BFPBM was tested and the hydration mechanism of the PSA was analyzed. Results: The results show that when the specific surface area (SSA) of SS is 457 m2ˑkg-1, the paste mass concentration (PMC) is 79%, the mixing ratio of PSA is 20%, and the mix proportion of PSA is SS: FGDG: GBFS = 58:10:32. In this case, water-reducing agent (WRA) accounting for 0.18% of the total amount of PSA is added. The 28d compressive strength of BFPBM is greater than 0.40 MPa with the maximum value of 6.22 MPa, and the mixture slump of BFPBM is greater than 215 mm, which meets the index requirements of Chinese National Standard T/CECS 1037-2022 Technical Standard for Backfilling Project by Using Premixed Fluidized Solidified Soil. Discussion: According to the mechanism study, the mineral phases of the PSA after hydration are: C2S, C3S, Ca (OH)2, ettringite (AFT), C-S-H gel, and RO phase. C2S, C3S, CaSO4 and other substances gradually disappeared with the hydration, while the content of AFt and C-S-H gel substances increased. BFPBM prepared from iron and steel waste has high strength and environmental friendliness, making it have good application prospects in foundation pit backfilling and mine filling.